Compound for injection molding
Patent Information
- Application Number
- JP2023138343
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-12
AI Technical Summary
【0016】 本発明による射出成形用コンパウンドは、以下の特徴を備えている:射出成形用コンパウンドは、球状の軟磁性体粉末と、ポリフェニレンスルフィド(PPS)樹脂と、半芳香族ポリアミド(PPA)樹脂とを含んでいる;PPS樹脂とPPA樹脂との重量比は、90:10~60:40となっている。これにより、本発明の射出成形用コンパウンドは、射出成形の際に必要な流動性を確保しつつ、射出形成後の金型のスプルー内やランナー内で固化したコンパウンドに割れが発生しないようになっている。即ち、本発明の射出成形用コンパウンドは、軟磁性体粉末を含む射出成形用コンパウンドに最適な構成を有している。
Smart Images

Figure 2025032853000001 
Figure 2025032853000002 
Figure 2025032853000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to an injection molding compound containing soft magnetic powder. [Background technology]
[0002] Patent Document 1 discloses a bonded magnet compound formed by kneading two types of resin, polyphenylene sulfide (PPS) resin and polyamide (PA) resin, with magnet powder (hard magnetic powder) while heating in a nitrogen atmosphere in order to achieve both the fluidity of the compound during injection molding and the strength and heat resistance of the molded body. Patent Document 1 lists ferrite magnet powder as an example of the hard magnetic powder contained in the bonded magnet compound. Patent Document 1 also discloses that the hard magnetic powder is coated with PA resin, and that if the PA resin content in the bonded magnet compound exceeds 2 wt%, the effect of moisture absorption by the PA resin becomes significant, resulting in oxidation and degradation of the hard magnetic powder, i.e., the metal powder. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2013-77802 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention aims to identify and provide an optimum composition for an injection molding compound that contains soft magnetic powder instead of hard magnetic powder. [Means for solving the problem]
[0005] In soft magnetic powders, strain accumulates when the amorphous solidifies during the manufacturing process. Furthermore, when manufacturing injection-molded products from soft magnetic powder and resin, even when the soft magnetic powder is mixed and molded with a low-melting-point PA resin, the low heat resistance of the low-melting-point PA resin prevents the mixing and molding temperatures from being increased due to the problem of gas generation caused by thermal decomposition of the low-melting-point PA resin and the resulting decrease in resin strength. This inevitably results in low heating temperatures during the mixing and molding processes, making it more likely that new strain will occur in the soft magnetic powder. On the other hand, when the soft magnetic powder is mixed and molded with a high-melting-point resin during the mixing and molding processes, the high heating temperatures relieve the strain generated during the manufacturing process and make it less likely that new strain will occur in the soft magnetic powder. Therefore, injection molding compounds containing soft magnetic powder must contain a high-melting point resin in order to alleviate distortion that occurs during the manufacturing process of the soft magnetic powder and to suppress the generation of new distortion in the soft magnetic powder during the kneading process of the soft magnetic powder and the molding process.
[0006] The bonded magnet compound of Patent Document 1 contains a high-melting point PPS resin, which is intended to provide preventative heat resistance to the molded body in anticipation of its use at high temperatures. On the other hand, injection molding compounds containing soft magnetic powder must contain a high-melting point resin to alleviate distortions generated during the manufacturing process of the soft magnetic powder and to prevent new distortions from occurring in the soft magnetic powder during the mixing and molding processes of the soft magnetic powder and resin. Patent Document 1 also addresses the issue of oxidative degradation of the metal powder contained in the bonded magnet compound. However, even when the compound containing the soft magnetic powder itself is heat-treated, oxidative degradation of the soft magnetic powder (metal powder contained in the compound) is a concern. However, if the soft magnetic powder and resin are mixed in a nitrogen atmosphere as in Patent Document 1 to avoid oxidative degradation of the soft magnetic powder contained in the compound due to heating, the manufacturing cost of the compound would increase.
[0007] Taking these into consideration, the inventors of the present application have devised an injection molding compound containing PPS resin, semi-aromatic polyamide (PPA) resin, which is a type of PA resin, and soft magnetic powder, in which the soft magnetic powder contained in the compound is spherical like atomized powder and is coated with an insulating coating such as a glass coating. In this proposed injection molding compound, the soft magnetic powder is coated with an insulating coating, so that the soft magnetic powder does not deteriorate due to oxidation even when the compound is heat-treated in air, and the possibility of the soft magnetic powder deteriorating due to moisture absorption by the PPA resin is also reduced.
[0008] On the other hand, the inventors of the present application realized that unless the blending ratio of PPA resin to PPS resin is increased to a certain extent, the compound would not have the necessary fluidity during injection molding and the strength of the injection-molded product would not be ensured. They also realized that if the blending ratio of PPA resin to PPS resin is too high, cracks would occur in the compound that solidified in the sprue or runner of the mold after injection molding. Therefore, the inventors of the present application devised a blending ratio of PPA resin to PPS resin that is relatively higher than the blending ratio of PA resin to PPS resin in the compound of Patent Document 1, while setting a certain upper limit, thereby completing the present invention. Furthermore, since the compound of the present application contains the insulation-coated soft magnetic powder described above, even if the blending ratio of PPA resin to PPS resin is increased, the compound is less likely to suffer from the same problem of oxidative degradation of the soft magnetic powder due to moisture absorption by the PA resin as that of the compound of Patent Document 1, i.e., oxidative degradation of the soft magnetic powder due to moisture absorption by the PPA resin.
[0009] That is, the present invention provides a first injection molding compound comprising: An injection molding compound comprising spherical soft magnetic powder, polyphenylene sulfide (PPS) resin, and semi-aromatic polyamide (PPA) resin, The soft magnetic powder is coated with an insulating material, The content of the soft magnetic powder in the injection molding compound is 60 vol% or more, The weight ratio of the PPS resin to the PPA resin is 90:10 to 60:40. An injection molding compound is provided.
[0010] The present invention also provides a second injection molding compound, which is the first injection molding compound, The PPA resin contains, as monomer units, a diamine having 9 or more carbon atoms and terephthalic acid. An injection molding compound is provided.
[0011] The present invention also provides a third injection molding compound, which is the second injection molding compound, The weight ratio of the PPS resin to the PPA resin is 80:20 to 60:40. An injection molding compound is provided.
[0012] The present invention also provides a fourth injection molding compound, which is the first injection molding compound, the injection molding compound includes a coupling agent; The content of the coupling agent in the injection molding compound is 0.01 wt% to 2 wt%. An injection molding compound is provided.
[0013] The present invention also provides a fifth injection molding compound, which is the first injection molding compound, The particle size of the soft magnetic powder is 1 μm to 100 μm, The crystallinity of the soft magnetic powder is 0 to 60%, The content of initial precipitates in the soft magnetic powder is 5 vol% or less, The aspect ratio of the soft magnetic powder is 0.4 to 1.0, No sharp-angled protrusions are formed on the surface of the soft magnetic powder. An injection molding compound is provided.
[0014] The present invention also provides a sixth injection molding compound, which is the first injection molding compound, The soft magnetic powder is an amorphous alloy powder or an Fe-based nanocrystalline alloy powder. An injection molding compound is provided.
[0015] The present invention also provides a seventh injection molding compound, which is the first injection molding compound, The insulating coating is made of heat-resistant inorganic glass. An injection molding compound is provided. [Effects of the Invention]
[0016] The injection molding compound of the present invention has the following characteristics: the injection molding compound contains spherical soft magnetic powder, polyphenylene sulfide (PPS) resin, and semi-aromatic polyamide (PPA) resin; the weight ratio of PPS resin to PPA resin is 90:10 to 60:40. This ensures that the injection molding compound of the present invention has the fluidity required for injection molding, while preventing cracks from occurring in the compound that solidifies in the sprue or runner of the mold after injection molding. In other words, the injection molding compound of the present invention has an optimal configuration for an injection molding compound containing soft magnetic powder. DETAILED DESCRIPTION OF THE INVENTION
[0017] The present invention will be described below through embodiments of the invention, but the invention according to the claims is not limited to the following embodiments. For clarity of explanation, the following description has been simplified as appropriate. Note that unless otherwise specified, the symbol "to" indicating a numerical range includes the lower limit and the upper limit.
[0018] The injection molding compound according to an embodiment of the present invention is used to injection mold a soft magnetic core. Compared to a soft magnetic core obtained by compression molding a soft magnetic powder, a soft magnetic core obtained by injection molding is manufactured by suppressing the pressure applied to the soft magnetic powder during manufacturing, thereby suppressing distortion accumulated in the soft magnetic core. Therefore, a soft magnetic core obtained by injection molding can reduce core loss compared to a soft magnetic core obtained by compression molding a soft magnetic powder.
[0019] The injection molding compound of this embodiment contains spherical soft magnetic powder, polyphenylene sulfide (PPS) resin, and semi-aromatic polyamide (PPA) resin.
[0020] (Soft magnetic powder) The content of the soft magnetic powder in the injection molding compound of this embodiment is 60 vol% or more. The crystallinity of the soft magnetic powder of this embodiment is 0 to 60%. The soft magnetic powder of this embodiment is an amorphous alloy powder or an Fe-based nanocrystalline alloy powder. The present invention is not limited thereto. The soft magnetic powder can be appropriately selected from materials exhibiting soft magnetism. Powders made of one or more metals selected from soft magnetic iron, silicon steel, Fe-Al alloy, permendur (Fe-Co alloy), Sendust, permalloy-based alloys (78 permalloy, supermalloy, mumetal, hardperm), Fe-based amorphous alloys, and Fe-based nanocrystalline alloy powders can be used. The amorphous alloy powder refers to an amorphous alloy that does not have a crystalline structure, and the Fe-based amorphous alloy powder refers to an amorphous alloy that does not have a crystalline structure, among Fe-based alloys. The Fe-based nanocrystalline alloy powder is an alloy obtained by heat-treating the Fe-based amorphous alloy powder to precipitate fine α-Fe crystals in the amorphous phase. The soft magnetic powder can be used alone or in combination of two or more types.
[0021] The soft magnetic powder of this embodiment is an atomized powder and is spherical. That is, the soft magnetic powder of this embodiment is not a ferrite powder obtained by pulverizing ferrite. Methods for producing atomized powder include, for example, gas atomization, water atomization, centrifugal atomization, and plasma atomization, and gas atomization or water atomization is preferred from the viewpoint of mass production stability and productivity. During this manufacturing process, strain accumulates in the soft magnetic powder when the amorphous solidifies.
[0022] Generally, when producing soft magnetic powders with an amorphous phase as the primary phase, the precipitation of fine crystals (initial precipitates) of compound phases consisting of αFe(-Si), Fe-B, or Fe-P can occur due to factors such as insufficient rapid cooling during the cooling process of the molten metal, insufficient amorphous-forming ability determined by the elemental composition of the soft magnetic powder, or the influence of impurities contained in the raw materials. These initial precipitates can contribute to the degradation of the magnetic properties of the Fe-based nanocrystalline alloy powder. Specifically, these initial precipitates can cause the precipitation of nanocrystals with a particle size exceeding 50 nm in the Fe-based nanocrystalline alloy powder. Even a small amount of nanocrystals with a particle size exceeding 50 nm can inhibit domain wall motion and degrade the magnetic properties of the Fe-based nanocrystalline alloy powder. Furthermore, because the precipitated compound phases have poor soft magnetic properties, their presence alone significantly degrades the magnetic properties of the Fe-based nanocrystalline alloy powder. Therefore, it is generally considered desirable to reduce the content of initial precipitates in the soft magnetic powder as much as possible to produce a soft magnetic powder consisting essentially of only an amorphous phase. For these reasons, the content of initial precipitates in the soft magnetic powder is preferably 5 vol% or less. Note that this initial crystallinity is the volume ratio of the total initial crystalline components to the entire soft magnetic powder.
[0023] The crystallinity and initial precipitate content can be calculated by analyzing the results of X-ray diffraction (XRD) measurements using the Whole-Powder-Pattern Decomposition (WPPD) method. Furthermore, the peak positions of the X-ray diffraction results allow identification of precipitate phases such as the αFe(-Si) phase and compound phases.
[0024] The soft magnetic powder of this embodiment has no acute-angled protrusions on its surface. The aspect ratio of the soft magnetic powder is 0.4 to 1.0. This aspect ratio refers to the ratio of the length in the minor axis direction to the length in the major axis direction of the soft magnetic powder particle. Specifically, the cross sections of a plurality of particles (e.g., 10 to 60 particles) of the soft magnetic powder are observed with an SEM (scanning electron microscope), the lengths in the minor axis direction and the major axis direction are measured, and the aspect ratio of each particle is calculated. The average of the aspect ratios of the plurality of particles thus calculated is defined as the aspect ratio of the soft magnetic powder.
[0025] The particle size of the soft magnetic powder of this embodiment is 1 μm to 100 μm. The particle size is the median diameter D50, and is a value measured using a laser diffraction / scattering method.
[0026] The soft magnetic powder of this embodiment is coated with an insulating coating. The insulating coating is made of heat-resistant inorganic glass, specifically silicate glass, borate glass, borosilicate glass, phosphate glass, bismuth glass, etc. Note that the present invention is not limited thereto, and the insulating coating material may be, for example, inorganic oxides such as SiO2 (silicic acid), Al2O3 (alumina), and ZrO2, inorganic nitrides such as Si3N4 and BN, aluminum dihydrogen triphosphate, or minerals such as mica and clay. Furthermore, the insulating coating material may be used alone or in combination of two or more types.
[0027] The soft magnetic powder of this embodiment is insulated as described above, so that the soft magnetic powder does not oxidize even when heat treated in the atmosphere.
[0028] As a method for insulatingly coating the soft magnetic powder, a dry thin film forming method such as sputtering can be used instead of a wet thin film forming method such as a sol-gel method.
[0029] When the soft magnetic powder is a ferrite powder obtained by pulverizing ferrite, it is difficult to provide an appropriate insulating coating. However, when the soft magnetic powder is an atomized powder, as in the soft magnetic powder of the present embodiment, the surface of the soft magnetic powder is spherical, making it relatively easy to provide an insulating coating with a glass coating or the like.
[0030] (PPS resin) The PPS resin of this embodiment is a linear PPS resin or a crosslinked PPS resin.
[0031] (PPA resin) The PPA resin of the present embodiment contains diamine and terephthalic acid as monomer units.
[0032] The diamine as a monomer unit constituting the PPA resin of the present embodiment has 9 or more carbon atoms, which makes the PPA resin of the present embodiment less susceptible to moisture absorption.
[0033] The diamine as a monomer unit constituting the PPA resin of the present embodiment is an aliphatic diamine.
[0034] Specific examples of PPA resins include poly(nonamethylene terephthalamide) (PA9T), poly(decamethylene terephthalamide) (PA10T), poly(undecamethylene terephthalamide) (PA11T), and poly(dodecamethylene terephthalamide) (PA12T). Of these, polynonamethylene terephthalamide (PA9T) is preferred.
[0035] In the injection molding compound of this embodiment, the weight ratio of PPS resin to PPA resin is 90:10 to 60:40. That is, the weight ratio of PPA resin in the entire mixed resin of PPS resin and PPA resin is 10% or more and 40% or less. If the weight ratio of PPA resin in the entire mixed resin of PPS resin and PPA resin is less than 10%, the mixed resin of PPS resin and PPA resin has low fluidity and it is difficult to ensure the strength of the solidified product of the mixed resin of PPS resin and PPA resin. For this reason, the weight ratio of PPA resin in the entire mixed resin of PPS resin and PPA resin needs to be 10% or more. Furthermore, if the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin exceeds 40%, the mixed resin of PPS resin and PPA resin cannot maintain its tenacity at high temperatures, and cracks occur in the compound solidified in the sprue and runner of the mold after injection molding. Therefore, the weight ratio of PPA resin in the entire mixed resin of PPS resin and PPA resin must be 40% or less.
[0036] The injection molding compound of this embodiment has the above weight ratio of PPS resin and PPA resin, so it ensures the fluidity required for injection molding while preventing cracks from forming in the compound that solidifies in the sprue or runner of the mold after injection molding. In other words, the injection molding compound of this embodiment has an optimal configuration for an injection molding compound that contains soft magnetic powder.
[0037] As described above, the soft magnetic powder of this embodiment is insulated, so even if the PPA resin in the injection molding compound absorbs moisture, the possibility of the soft magnetic powder being oxidized and deteriorated by this moisture absorption is reduced. As a result, the blending ratio of PPA resin to PPS resin in the injection molding compound of this embodiment is relatively higher than the blending ratio of PA resin to PPS resin in the compound of Patent Document 1, and the injection molding compound of this embodiment has higher fluidity than the compound of Patent Document 1.
[0038] Furthermore, if the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin is 20% or more, the mixed resin of PPS resin and PPA resin has high fluidity, which is more preferable. That is, the weight ratio of PPS resin to PPA resin is more preferably 80:20 to 60:40.
[0039] The injection molding compound of this embodiment contains a coupling agent. However, the present invention is not limited thereto, and the injection molding compound does not necessarily contain a coupling agent. However, if the injection molding compound contains a coupling agent, the wettability of the surface of the soft magnetic powder is increased, and the compatibility between the soft magnetic powder and the PPA resin and the compatibility between the soft magnetic powder and the PPS resin are both improved, which is more preferable.
[0040] (coupling agent) The coupling agent in this embodiment is a silane coupling agent. However, the present invention is not limited thereto, and the coupling agent may be a titanium coupling agent or other coupling agent. As described above, the soft magnetic powder in this embodiment is insulated, making it easier to coat the soft magnetic powder with a coupling agent. If the content of the coupling agent in the injection molding compound exceeds 2 wt%, the mixed resin of PPS resin and PPA resin may be denatured, or the layer formed on the insulating coating by the coupling agent may peel off or break. For this reason, the content of the coupling agent in the injection molding compound is preferably 0.01 wt% to 2 wt%.
[0041] The injection molding compound of this embodiment contains a flow improver, but the present invention is not limited to this, and the injection molding compound does not necessarily contain a flow improver.
[0042] The injection molding compound of this embodiment may further contain other components as long as the effects of the present invention are achieved. Examples of other components include antioxidants, lubricants, UV absorbers, metal deactivators, HALS, stabilizers, plasticizers, flame retardants, nucleating agents, fillers, compatibilizers, curing agents, photoinitiators, antistatic agents, anti-fog agents, conductive agents, clarifying agents, lubricants, antibacterial agents, and other functional agents. These may be used alone or in combination of two or more.
[0043] The injection molding compound of this embodiment is manufactured, for example, as follows. First, alloy powder obtained by atomization is heat-treated to produce an Fe-based nanocrystalline alloy powder as soft magnetic powder. The surface of this soft magnetic powder is then insulated with an insulating coating agent, and the surface of the insulated soft magnetic powder is then further coated with a coupling agent to produce a surface-treated soft magnetic powder. Finally, this surface-treated soft magnetic powder, PPS resin, PPA resin, and flowability improver are kneaded and pelletized in air while being heated at a temperature equal to or higher than the melting point of the PPS resin or the PPA resin, to obtain the injection molding compound.
[0044] As described above, the injection molding compound of this embodiment is manufactured by heating and kneading a soft magnetic powder that has been previously insulated with a resin. This prevents the soft magnetic powder from being oxidized even when the soft magnetic powder and resin are heated and kneaded in the air. That is, in the manufacturing method of the injection molding compound of this embodiment, the soft magnetic powder and resin are heated and kneaded in the air, which is less expensive, rather than in a nitrogen atmosphere, which increases manufacturing costs, as in Patent Document 1.
[0045] When injection molding is performed using the injection molding compound of this embodiment, the injection molding compound may be injection molded in accordance with a conventional method while being heated to a temperature equal to or higher than the melting point of the PPS resin or the melting point of the PPA resin, whichever is higher.
[0046] As described above, in soft magnetic powders, strain accumulates when the amorphous solidifies during the manufacturing process. Furthermore, when soft magnetic powder is mixed with a low-melting-point PA resin or the like and injection-molded, the low-melting-point PA resin has low heat resistance. This prevents the mixing and molding temperatures from being increased due to the problem of gas generation caused by thermal decomposition of the low-melting-point PA resin and the resulting decrease in resin strength. This inevitably results in lower heating temperatures during the mixing and molding processes, making new strain more likely to occur in the soft magnetic powder. On the other hand, when an injection-molded body is manufactured using the injection molding compound of this embodiment, the heating temperature increases during the mixing and molding processes due to the high melting point of the mixed resin contained in the injection molding compound. This alleviates the strain generated during the manufacturing process of the soft magnetic powder, and new strain is less likely to occur in the soft magnetic powder. This means that the injection molding compound of this embodiment can produce an injection-molded body (injection core) with reduced core loss.
[0047] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0048] <Preparation of injection molding compound> First, the raw materials for producing soft magnetic powder were prepared: industrially pure iron, ferrosilicon, ferrophosphorus, ferroboron, ferroniobium, ferromolybdenum, zirconium, tantalum, tungsten, hafnium, titanium, ferrovanadium, ferrochromium, ferromanganese, ferrocarbon, ferroaluminum, iron sulfide, and electrolytic copper. The raw materials were weighed to obtain the desired composition and melted by high-frequency induction in an argon atmosphere to produce a molten alloy. The molten alloy was then processed by water atomization to produce Fe-Si-BP-Cu alloy powder.
[0049] The content of the initial precipitates in the obtained alloy powder was calculated by the above-mentioned method using XRD and was found to be 0 vol %.
[0050] Next, the obtained alloy powder was heat-treated in a nitrogen atmosphere using an electric furnace to produce an Fe-based nanocrystalline alloy powder as a soft magnetic powder. The particle size of the obtained soft magnetic powder was measured using a laser particle size distribution analyzer, and the median diameter D50 was 33 μm. The crystallinity of the obtained soft magnetic powder was calculated using the above-mentioned XRD method and was found to be 37%. In addition, the aspect ratio of the obtained soft magnetic powder was measured using the above-mentioned SEM method and was found to be 0.8 (n = 10 average).
[0051] This soft magnetic powder was coated with a phosphoric acid-based inorganic insulating agent as an insulating coating agent to form an insulating coating. This insulating-coated soft magnetic powder was mixed with a silane coupling agent, and the insulating-coated soft magnetic powder was further coated with the coupling agent.
[0052] The soft magnetic powder coated with the coupling agent, a linear (semi-linear) polyphenylene sulfide (PPS) resin (melting point: 280°C), a polynonamethylene terephthalamide (PA9T) resin (melting point: 306°C), and a flowability improver were then kneaded while heating at approximately 330°C, and the resulting mixture was pelletized to form the injection molding compounds of Examples 1 to 3 and Comparative Examples 1 to 4. Table 1 shows the volumetric proportion of the soft magnetic powder in the injection molding compounds of Examples 1 to 3 and Comparative Examples 1 to 4, the volumetric proportion of the mixture of the PPS resin and PA9T resin mixed resin and the flowability improver in the injection molding compounds, the weight ratio of the PPS resin to the PA9T resin, the volumetric proportion of the insulating coating agent in the injection molding compounds, and the volumetric proportion of the silane coupling agent in the injection molding compounds.
[0053] [Table 1]
[0054] <MFR measurement of injection molding compounds> The melt flow rate (MFR) of the injection molding compounds of Examples 1 to 3 and Comparative Examples 1 to 4 was measured in accordance with the thermoplastic plastic flow test method specified in JIS K7210 using a half-size die, by measuring the flow rate three times per 10 minutes at a test temperature of 330°C under a test load of 20 kg. The measurement results are shown in Table 2.
[0055] [Table 2]
[0056] As can be seen from Table 2, in Examples 1 to 3, where the weight ratio of PPS resin to PA9T resin was 90:10 to 60:40, the melt flow rate (MFR) was 157.0 to 202.7 g / 10 min, while in Comparative Examples 1 and 2, where the weight ratio of PPS resin to PA9T resin was 100:0 and 95:5, the melt flow rate (MFR) was 124.4 g / 10 min and 123.6 g / 10 min, respectively, which are lower than those in Examples 1 to 3. This shows that injection molding compounds in which the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin is 10% or more have significantly improved fluidity compared to injection molding compounds in which the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin is less than 10%.
[0057] <Injection core production> Molds were prepared to obtain the injection-molded articles (injection cores) of Examples 1 to 3 and Comparative Examples 1 to 4, i.e., cavity dimensions of 13 mm outer diameter, 8 mm inner diameter, and 5 mm height. The injection molding compounds of Examples 1 to 3 and Comparative Examples 1 to 4 were heated and melted at approximately 330°C, and the molten injection molding compounds were injected into the cavities through the sprue, runner, and gate to obtain the injection cores of Examples 1 to 3 and Comparative Examples 1 to 4. The solidified compounds (solidified material) in the sprue and runner of the mold after injection molding were visually inspected for cracks and evaluated. The evaluation results are shown in Table 3.
[0058] <Evaluation of injection core> The injected cores of Examples 1 to 3 and Comparative Examples 1 to 4 were evaluated by the following method. First, a winding was applied to the injected core, and then the magnetic permeability μ of the injected core was measured using an LCR meter at 100 kHz and an applied magnetic field of 0 A / m. The core loss Pcv of the injected core was also measured at a frequency of 20 kHz and a magnetic flux density of 100 mT. Furthermore, the radial crushing strength of the injected core was calculated using formula (1) by performing a compression test in accordance with the radial crushing strength testing method of JIS Z2507. K = [F × (De)] / (L × e 2 ):Formula (1) K: Radial crushing strength (MPa) F: Maximum load at break (N) L: Length of hollow cylinder (mm) D: Outer diameter of hollow cylinder (mm) e: Wall thickness of hollow cylinder (mm) The measurement results are shown in Table 3.
[0059] [Table 3]
[0060] Table 3 shows that the magnetic permeability μ of Examples 1 to 3, in which the weight ratio of PPS resin to PA9T resin was 90:10 to 60:40, was 19.0 to 19.4, while the magnetic permeability μ of Comparative Examples 1 and 2, in which the weight ratio of PPS resin to PA9T resin was 100:0 and 95:5, was 17.9 and 18.7, respectively, which were lower than those of Examples 1 to 3. This shows that injected cores in which the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin was 10% or more had a higher magnetic permeability μ than injected cores in which the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin was less than 10%.
[0061] Furthermore, from Table 3, the core loss Pcv of Examples 1 to 3, in which the weight ratio of PPS resin to PA9T resin is 90:10 to 60:40, is 173.1 to 205.3 kW / m 3On the other hand, the core loss Pcv of Comparative Example 2, in which the weight ratio of PPS resin to PA9T resin is 95:5, is 212.1 kW / m 3 This was found to be a higher value than Examples 1 to 3. This shows that an injected core in which the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin is 10% or more has a lower core loss Pcv than an injected core in which the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin is 5%.
[0062] Additionally, Table 3 shows that the radial crushing strengths of Examples 1 to 3, in which the weight ratio of PPS resin to PA9T resin was 90:10 to 60:40, were 51.6 to 53.3 MPa, while the radial crushing strengths of Comparative Examples 1 and 2, in which the weight ratio of PPS resin to PA9T resin was 100:0 and 95:5, were 49.1 MPa and 48.7 MPa, respectively, which were lower than those of Examples 1 to 3. This shows that injected cores in which the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin was 10% or more had higher radial crushing strength than injected cores in which the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin was less than 10%.
[0063] Furthermore, Table 3 shows that in Examples 1 to 3, where the weight ratio of PPS resin to PA9T resin was 90:10 to 60:40, no cracks occurred in the compound solidified in the sprue or runner, whereas in Comparative Examples 3 and 4, where the weight ratio of PPS resin to PA9T resin was 40:60 and 0:100, cracks occurred in the compound solidified in the sprue or runner. This shows that when the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin exceeds 40%, cracks occur in the compound solidified in the sprue or runner of the mold after injection molding, whereas when the weight ratio of PPA in the entire mixed resin of PPS resin and PPA resin is 40% or less, no cracks occur in the compound solidified in the sprue or runner of the mold after injection molding.
[0064] Although the best mode for carrying out the present invention has been described, it will be apparent to those skilled in the art that modifications can be made to the present invention without departing from the spirit of the present invention, and such modifications are within the scope of the present invention.
Claims
1. An injection molding compound comprising spherical soft magnetic powder, polyphenylene sulfide (PPS) resin, and semi-aromatic polyamide (PPA) resin, The soft magnetic powder is coated with an insulating material, The content of the soft magnetic powder in the injection molding compound is 60 vol% or more, The weight ratio of the PPS resin to the PPA resin is 90:10 to 60:
40. Injection molding compound.
2. 2. The injection molding compound of claim 1, The PPA resin contains, as monomer units, a diamine having 9 or more carbon atoms and terephthalic acid. Injection molding compound.
3. 3. The injection molding compound according to claim 2, The weight ratio of the PPS resin to the PPA resin is 80:20 to 60:
40. Injection molding compound.
4. 2. The injection molding compound of claim 1, The injection molding compound includes a coupling agent, The content of the coupling agent in the injection molding compound is 0.01 wt % to 2 wt %. Injection molding compound.
5. 2. The injection molding compound of claim 1, The particle size of the soft magnetic powder is 1 μm to 100 μm, The crystallinity of the soft magnetic powder is 0 to 60%, The content of initial precipitates in the soft magnetic powder is 5 vol% or less, The aspect ratio of the soft magnetic powder is 0.4 to 1.0, The soft magnetic powder has a surface free from acute-angled protrusions. Injection molding compound.
6. 2. The injection molding compound of claim 1, The soft magnetic powder is an amorphous alloy powder or an Fe-based nanocrystalline alloy powder. Injection molding compound.
7. 2. The injection molding compound of claim 1, The insulating coating is made of heat-resistant inorganic glass. Injection molding compound.
Citation Information
Patent Citations
Compound for bond magnet and bond magnet
JP2013077802A